The Relationship Between Self Regulated Learning and Academic Stress on Students Taking Skipsi Course at FPIP 2016/2017 Universitas Muhammadiyah Sidoarjo - Fatmawati Fatmawati; Ririn Dewanti (Universitas Muhammadiyah Sidoarjo, 2022)
Academic stress is stress related to educational activities that occur during the education period caused by demands that arise when a person is in education. This study aims to determine the relationship between self-regulated learning and academic stress in students taking thesis courses at FPIP in 2016. / 2017 Muhammadiyah University of Sidoarjo. This research is a type of quantitative research with a correlation approach. The population of this study were students who took the 2016/2017 thesis course at FPIP with a total of 387 students, with a research sample of 186 students taking 2016/2017 courses at FPIP, which were taken using a quota sampling technique. The data collection method used a Likert-model psychological scale, namely the academic stress scale (21 items, a = 0.834) and the self-regulated learning scale (68 items, a = 0.949). The data analysis used is the analysis with Pearson Product Moment correlation technique using the SPSS 18 for windows program. The results showed a negative relationship between self-regulated learning and academic stress in students who took thesis courses at FPIP in 2016/2017 Muhammadiyah University of Sidoarjo with a correlation coefficient of -0.376 with ρ = 0.000 (ρ <0.05). The correlation coefficient value shows that there is a significant negative relationship, meaning that the higher the self-regulated learning, the lower the academic stress. Conversely, the lower self-regulated learning, the higher the academic stress. Self regulated learning provides an effective contribution of 14.1% to academic stress